Pengaruh Budgetary Goal Characteristics, Komitmen Organisasi, Dan Motivasi Pada Kinerja Manajerial dengan Gaya Kepemimpinan Sebagai Variabel Moderasi - Misdiantari Aristiani, Ida Ayu; Sri Harta Mimba, Ni Putu (E-Jurnal Akuntansi; Vol 27 No 3 (2019), 2019)
This study aims to determine the effect of budgetary goal characteristics, organizational commitment, and motivation on managerial performance using transformational leadership style as a moderating variable. This research was conducted on the Denpasar City Government. The data analysis technique used is Test Moderated Regression Analysis. The population in this study amounted to 31 SKPD and the number of samples in this study were 93 people. Thi s  study concluded that 1) budgetary goal characteristics negatively affected managerial performance (significance 0.375); 2) organizational commitment has a positive effect on managerial performance (significance 0.081); 3) motivation has a positive effect on managerial performance (significance 0,000); 4) transformational leadership style can moderate (strengthen) the influence of budgetary goal characteristics on managerial performance (significance 0.034); 5) transformational leadership style cannot moderate (weaken) the influence of organizational commitment on managerial performance (significance 0.769); 6) leadership style was able to moderate (strengthen) the effect of motivation on managerial performance (significance 0.003). Keywords: Budgetary goal characteristics, organizational commitment, motivation, managerial performance, transformational leadership style